Improved Supply Management, Production Planning and Control Through Material Requirements Planning and Master Production Schedule Tools in a Mype Dark Kitchen - Celi Chavez, Dora Antonella (2024)
The purpose of the research focused on the application of tools such as MRP and MPS in the hamburger process in a dark kitchen, with the objective of reducing the opportunity cost produced by unsold products due to lack of supplies. The improvement proposal was divided into two parts, the first with a focus on production planning and control and the second part, related to a new kitchen design. In addition, in order to design a new floor plan, the Guerchet method was used, as well as the relational diagram of activities. The investigation resulted in approximately 10% of additional incoming orders that could have been attended to in the month of October.